2021
DOI: 10.1371/journal.ppat.1009944
|View full text |Cite
|
Sign up to set email alerts
|

Protective CD4+ Th1 cell-mediated immunity is reliant upon execution of effector function prior to the establishment of the pathogen niche

Abstract: Intracellular infection with the parasite Leishmania major features a state of concomitant immunity in which CD4+ T helper 1 (Th1) cell-mediated immunity against reinfection coincides with a chronic but sub-clinical primary infection. In this setting, the rapidity of the Th1 response at a secondary site of challenge in the skin represents the best correlate of parasite elimination and has been associated with a reversal in Leishmania-mediated modulation of monocytic host cells. Remarkably, the degree to which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Studies in leishmanization models demonstrated that protection upon challenge with L. major parasites is mediated by the TRM cells that help recruit heterogenous cell populations including CD4 + T effector cells and inflammatory monocytes to the site of infection and mediate parasite control 19,20 . Prior studies in leishmanization models also showed the critical role of IFNγ secreting CD4 + CD44 + Ly6C + T effector cells in protection against challenge by virtue of their capacity to mount microbicidal activities immediately after challenge 28,29 . However, since the presence of "ready-to-act" CD4 + CD44 + Ly6C + T effector cells requires a persistent infection of Leishmania parasites, achieving durable protection through safer vaccination methods makes TRM populations more desirable to target.…”
Section: Discussionmentioning
confidence: 98%
“…Studies in leishmanization models demonstrated that protection upon challenge with L. major parasites is mediated by the TRM cells that help recruit heterogenous cell populations including CD4 + T effector cells and inflammatory monocytes to the site of infection and mediate parasite control 19,20 . Prior studies in leishmanization models also showed the critical role of IFNγ secreting CD4 + CD44 + Ly6C + T effector cells in protection against challenge by virtue of their capacity to mount microbicidal activities immediately after challenge 28,29 . However, since the presence of "ready-to-act" CD4 + CD44 + Ly6C + T effector cells requires a persistent infection of Leishmania parasites, achieving durable protection through safer vaccination methods makes TRM populations more desirable to target.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, it has been demonstrated that protection upon challenge with L. major parasites in healed (i.e., leishmanization) is mediated by the TRM cells that help recruit heterogenous cell populations including CD4 + T-effector cells and inflammatory monocytes to the site of infection and mediate parasite control ( 19 , 20 ). Prior studies in leishmanization models also showed the critical role of IFNγ-secreting CD4 + CD44 + Ly6C + T effector cells in protection against challenge by virtue of their capacity to mount microbicidal activities immediately after challenge ( 28 , 29 ). However, since the presence of “ready-to-act” CD4 + CD44 + Ly6C + T-effector cells requires a persistent infection of Leishmania parasites, achieving durable protection through safer vaccination methods makes TRM populations more desirable to target.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this concept, Zhang et al 25 , using a CRISPR genome edited L. major strain ( LmCen −/− ), demonstrated that wildtype L. major infected/healed (leishmanization) and LmCen −/− immunized mice presented high percentage of T CD4 + memory cells producing IFN-γ. The low levels of persistent antigens may be important for maintaining long term protection profile, as the generation of IFN-γ producing CD4 + T effector populations 25 , 78 , despite the difference between the survival profile of parasites used in leishmanization and immunization with attenuated parasites. Independently T CM and skin resident T RM memory T cells were also shown to play a role in protection in L. major mouse models 39 , 79 .…”
Section: Discussionmentioning
confidence: 99%